Lethal injuries on the scaphitid ammonoid Hoploscaphites nicolletii (Morton, 1842) in the Upper Cretaceous Fox Hills Formation, South Dakota, USA - Amane Tajika; Anastasia Rashkova; Neil H. Landman; Adiël A. Klompmaker (Swiss Journal of Palaeontology)
Abstract Predator–prey relationships are considered a major driver for the evolution of organisms, and thus contributed to shaping morphology, ecology, and diversity. During the Late Cretaceous of North America, ammonoid cephalopods were one of the most abundant and diverse marine invertebrates. Despite frequent reports of shell breakage in ammonoids, little is known pertaining to the frequency, position, and size of the shell break through a stratigraphic succession. In this study, we analyze an extensive collection of the scaphitid ammonoid Hoploscaphites nicolletii, which exhibits shell breakage, from the Upper Cretaceous (Maastrichtian) Fox Hills Formation in South Dakota, USA. We focus on four upper Maastrichtian assemblage zones listed stratigraphically from bottom to top—the lower nicolletii Assemblage Zone (LNAZ), the Limopsis-Gervillia Assemblage Zone (LGAZ), the upper nicolletii Assemblage Zone (UNAZ), and the Protocardia-Oxytoma Assemblage Zone (POAZ). Within the collection, we observed two primary types of breakage: ventral and lateral, each displaying a relatively consistent geometry. Lateral breaks, measuring a few centimeters, represent about 20–40% of the maximum conch diameter. Ventral breaks are slightly larger, representing 30–70% of the diameter. Both breakage types occur in the body chamber at approximately 90° from the aperture extending to near the last septum. We find that the incidence of injury increased from 6.6 to 13.7% with some fluctuation across the zones. The breakage size relative to body size does not exhibit a clear change across the assemblage zones. Additionally, no significant difference is apparent in the body size between injured and uninjured specimens within each zone. A weak positive correlation between the size of lateral breaks and maximum conch diameter in LNAZ suggests a tendency for larger predators to target larger individuals. Given the consistency of geometry and size, we presume that these breaks represent lethal injuries from durophagous predators. We propose coleoid cephalopods as the likely culprits for ventral injuries, although fish and crustaceans are plausible alternatives. Concerning lateral injuries, decapod crustaceans appear to be the most probable durophagous predators.